Correlation Between Switching Costs and Customer Loyalty: Integration of AI in Theoretical and Practical Approaches - Galib, Mukhtar; Rijal, Syamsul; Gunawan, Aden; Maulana (Journal of Marketing Management and Innovative Business Review, 2024)
Abstract: This study explores the relationship between switching costs and customer loyalty, as well as how the integration of artificial intelligence (AI) can influence customer retention strategies. The findings suggest that high switching costs can enhance customer loyalty, particularly in industries that rely on long-term relationships. However, the loyalty that is formed tends to be calculative rather than affective, indicating that high switching costs do not always result in sustainable loyalty. The use of AI in customer management has proven to be more effective in managing switching costs and enhancing loyalty by offering more personalized experiences and reducing the negative perception of switching costs. The practical implication of these findings is that companies can leverage AI to develop more effective retention strategies that not only rely on switching costs but also on better customer experiences. This study contributes to the literature on the use of AI in retention strategies and customer loyalty